The Reflection Of Identity Through The Use Of Code-Mixing In Chinese Indonesian Family - Barbieta Lorenza Mertiafo (Samudra Ilmu Indonesia, 2026)
The use of code-mixing is a normal practice in multilingual societies and is useful in asserting social and cultural identities. Whereas, previous research has mainly focused on the code-mixing in the field of education or public discourse, there is not much research on the code-mixing in family communication for building identity. The purpose of this study was to explore the nature and functions of code-mixing in the family of Chinese-Indonesian family members and to analyze the coding phenomenon as an indicator of the family members' identities. The method used was qualitative ethnographic approach with one Chinese-Indonesian family located in Surabaya. The data were gathered by the use of participant observation, field notes, interviews, and analysis was conducted using Spradley's ethnographic approach. The results showed that the most frequent form of code-mixing was insertion, followed by alternation, and congruent lexicalization. The primary use of code-mixing was to convey emotions, to deepen family intimacy and solidarity, to maintain Chinese cultural heritage, to promote the educational communication, and to engage in daily communication. The findings revealed that the use of multilingual language was indicative of the family members' identities, with the integration of local, national and global language. In general, this study gives attention to the fact that code-mixing is not just a communicative activity, but also a process of building and sustaining a multilingual and multicultural identity in the Chinese-Indonesian family context.